Possibilities of using cubic spline function and yield-density models in estimation of live weight of kıvırcık lambs fed with different silage types - Ö. Şengül; Ş. Çelik; İ. Ak (Arquivo Brasileiro de Medicina Veterinária e Zootecnia, 2024)
ABSTRACT In this study, the possibilities of using Cubic Spline functions and some yield-density models in the estimation of live weights of Kıvırcık lambs fed with different silage types were investigated. In the experiment, 40 male Kıvırcık lambs aged 2.5-3 months were used and the animals were fattened for 56 days. To assess the predictive performance of the fitted models, model fit statistics such as the coefficient of determination (R2), adjusted R2, mean square error (MSE), and Akaike Information Criterion (AIC) were determined. The Cubic Spline model was discovered to be the best model for quantifying Kıvırcık lambs live weight, with the highest R2 and adjusted R2 values, as well as the lowest MSE and AIC values. Cubic Spline functions were applied as live weight estimation model in lambs fed with silage containing 5 different ratios of corn and sunflower (100% sunflower silage, 75% sunflower + 25% corn silage, 50% sunflower + 50% corn silage, 25% sunflower + 75% corn silage, 100% corn silage). As a result, Cubic Spline functions have been found to be effective in estimating the live weight of fattened lambs.